Seismic history of Pel la and the 1st century B.C. earthquake - Zamba, I.; Kouskouna, V. (Bulletin of the Geological Society of Greece, 2007)
Research and evaluation of past and recent seismic records is required in order to obtain an overall picture of the seismic history of a given region. To this aim, important information can be collected through the study of monuments and the damage that they may have experienced during their history. Consequently, the archaeological reports on a hitherto unknown earthquake of the Is' century B.C. in Pella (northern Greece) are particularly interesting. These reports are based on the findings that came to light after the excavations of I.Akamatis in the region where the ancient town of Pella was laying. Beginning with this earthquake, this study tries to reach useful conclusions on the seismicity of Pella, in terms of macroseismic intensities from all earthquakes that have affected the town. For all these events, the intensity attenuation relations were used to calculate the macroseismic intensity in Pella. Although it is known a priori that the area is characterized as a relatively low seismicity area, the picture of its seismic history indicates the existence of damaging earthquakes with relatively large return periods. More specifically, in Pella the maximum observed intensity was found to be 7/8 during its seismic history, indicating the picture of low-to-moderate seismic hazard in the region.